Triterpenoids from Ganoderma lucidum inhibit cytochrome P450 enzymes interfering with the metabolic process of specific clinical drugs - Li, Dawei; Lin, Yuxin; Lv, Xia; Wu, Yuzhuo; Han, Chaoyan; Cao, Peng; Zhang, Guixin; Leng, Aijing; Zhou, Jian; Wang, Chao (Frontiers in Pharmacology, 2024)
Background: Ganoderma lucidum (G. lucidum), which possesses various biological effects, has been widely used as traditional medicine and functional food in Asian countries, especially China. In consideration of its various biological effects on human health care, G. lucidum was usually used in combination with other drugs. However, the potential drug-drug interaction induced by G. lucidum through cytochrome P450 enzymes (CYPs) remain unknown. Methods: Using the in vivo activity assay of CYPs, the inhibitory effects of G. lucidum and its constituents could be evaluated. The interference of G. lucidum on the metabolic processes of clinical drugs could be investigated. The chemical constituents of G. lucidum could be identified using LC-MS. The interaction between bioactive compounds and CYPs could be proposed through in silico docking analysis and molecular dynamics. Results: The dichloromethane extract of G. lucidum could inhibit various CYP450 subtypes in vitro and interfere with the pharmacokinetics of four drugs in rats. Triterpenoids were identified as the main constituents of the dichloromethane extract by Q-TOF-MSn in preliminary analyses. Then, a triterpenoid library containing 66 compounds was established to evaluate their inhibitory effects against CYP 1A2, 2D6, 3A4, 2A6, 2B6, 2C9, and 2C19. CYP 1A2 was inhibited by most lanostane triterpenoids, indicating a strong affinity for these compounds. Among triterpenoids, compound 25 displayed a broad inhibitory effect against CYPs, except for CYP 3A4, 2D6, 2C9, and 2C19. Finally, compounds 6 and 25 exhibited interference with the metabolism of 16 drugs through the inhibition of CYPs in vitro. In silico molecular docking analyses for assaying the interaction between compound 25 and CYPs indicated that the hydrogen bonds formed between the hydroxyl groups and amino acid residues. Conclusion: G. lucidum displayed broad inhibitory effects on CYPs, with triterpenoids as the main bioactive constituents, which may induce potential drug-drug interaction. This information should be helpful for the rational use of G. lucidum in promoting human health.